Pengaruh Latihan Gated Obstacle Drill Dan Stair Step Roll Drill Terhadap Kemampuan Dribbling Pada Pemain U-12 SSB Putra Harapan - Rangga Panji Izzad; Martin Sudarmono; Mohamad Annas; Roas Irsyada (Indonesian Journal for Physical Education and Sport, 2024)
This research is motivated by the low level of basic dribbling skills possessed by U-12 SSB Putra Harapan players of Magelang City, which is caused by weak dribbling skills. The purpose of the study was to compare the results of gated obstacle drill and stair step roll drill on dribbling ability by obtaining two groups studied between pre-test and post-test and given different treatments. Based on the results of the research data, it can be concluded that the gated obstacle drill and stair step roll drill both affect the dribbling ability of the players. The gated obstacle drill is better than the stair step roll drill in improving dribbling ability seen from the value of the difference between the average pretest and posttest that has been done. It is expected to be used as a reference for football coaches in developing a training programme aimed at improving dribbling skills aimed at improving the ability of basic dribbling techniques.